2004
DOI: 10.1080/14622200412331324848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine and smoking on event‐related potentials: A review

Abstract: Event-related potentials can serve as an adjunct to reaction time in elucidating the effects of nicotine on rapid human information processing. We review the literature related to nicotine and event-related potentials. Although evidence indicates that, in the visual modality, nicotine enhances early perceptual processing and in certain instances speeding stimulus evaluation, the bulk of nicotine's effects seem to be on enhancing response preparation and response execution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 73 publications
(186 reference statements)
3
40
0
Order By: Relevance
“…16,17 Given that one of the most commonly reported reasons individuals use tobacco is to improve attention and arousal, [8][9][10][11] assessing N2, P3b, and alpha suppression before and after product usage may prove useful in objectively identifying which tobacco products elicit a preferential response. In line with this notion, previous research has shown that traditional cigarettes, or nicotine alone, can enhance alpha suppression, 18-21 N2, 22 and P3b amplitude. [22][23][24] EEG and ERPs have previously been used as a way to assess the effect of tobacco or nicotine on attention and brain state arousal.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…16,17 Given that one of the most commonly reported reasons individuals use tobacco is to improve attention and arousal, [8][9][10][11] assessing N2, P3b, and alpha suppression before and after product usage may prove useful in objectively identifying which tobacco products elicit a preferential response. In line with this notion, previous research has shown that traditional cigarettes, or nicotine alone, can enhance alpha suppression, 18-21 N2, 22 and P3b amplitude. [22][23][24] EEG and ERPs have previously been used as a way to assess the effect of tobacco or nicotine on attention and brain state arousal.…”
Section: Introductionsupporting
confidence: 58%
“…In line with this notion, previous research has shown that traditional cigarettes, or nicotine alone, can enhance alpha suppression, 18-21 N2, 22 and P3b amplitude. [22][23][24] EEG and ERPs have previously been used as a way to assess the effect of tobacco or nicotine on attention and brain state arousal. 18,23,[25][26][27][28][29][30] However, to our knowledge, this is the first study employing EEG in conjunction with traditional subjective measures of consumer acceptability in order to compare a variety of smokeless tobacco products.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…P300 Abnormalities in cocaine, methamphetamine, heroin addiction, and alcoholism. The P300 component of the ERP, occurring 300-to 600-msec poststimulus, is the most widely used ERP in psychiatry and other clinical applications (Polich & Herbst, 2000;Polich, Pollock, & Bloom, 1994;Pritchard, 1981Pritchard, , 1986Pritchard, Sokhadze, & Houlihan, 2004). The amplitude of the P300 reflects the allocation of attentional resources, whereas the latency is considered to reflect stimulus evaluation and classification time (Katayama & Polich, 1998;Polich & Herbst, 2000).…”
Section: Qeeg In Sudmentioning
confidence: 99%
“…Numerous studies have explored effects of smoking and nicotine on event related potentials (ERPs) [1,2], including selected ERP components [3] and the P300 [4]. Most of these studies reported increased amplitudes and/or decreased latencies supporting the hypothesis that nicotine generally enhances brain processing.…”
Section: Introductionmentioning
confidence: 98%